Promises and failures of gallium as an antibacterial agent. (March 2014) - Minandri, Fabrizia; Bonchi, Carlo; Frangipani, Emanuela; Imperi, Francesco; Visca, Paolo
ABSTRACT: : Gallium has a long history as a diagnostic and chemotherapeutic agent. The pharmacological properties of Ga(III) rely on chemical mimicry; when Ga(III) is exogenously supplied to living cells it can replace Fe(III) within target molecules, thereby perturbing bacterial metabolism. Ga(III)-induced metabolic distresses are dramatic in fast-growing cells, like bacterial cells. Interest in the antibacterial properties of Ga(III) has been raised by the compelling need for novel drugs to combat multidrug-resistant bacteria and by the shortage of new antibiotic candidates in the pharmaceutical pipeline. Ga(III) activity has been demonstrated, both in vitro and in animal models of infections, on several bacterial pathogens, also including intracellular and biofilm-forming bacteria. Ga(III) activity is affected by iron availability and the metabolic state of the cell, being maximal in iron-poor media and in respiring cells. Synergism between Ga(III) and antibiotics holds promise as last resort therapy for infections sustained by pandrug-resistant bacteria.